Regional Economic Outlook, October 2008, Western Hemisphere : Grappling with the Global Financial Crisis. (Regional Economic Outlook; Regional Economic Outlook, 2008)
The ongoing global turmoil represents a confluence of negative shocks for Latin America and the Caribbean: a freeze in global credit markets, weaker external demand, and lower commodity prices. But the region is expected to deal with these global shocks better than in previous crises, reflecting progress made in improving macroeconomic fundamentals over the past decade. Still, there are a number of downside risks going forward. Against this uncertain background, the report discusses the implications of the global financial crisis for the regional outlook and the corresponding challenges facing policymakers.